2014
DOI: 10.1159/000365155
|View full text |Cite
|
Sign up to set email alerts
|

Work Ability and Labor Supply after Kidney Transplantation

Abstract: Background: The vocational rehabilitation after kidney transplantation (KTX) is suboptimal. We sought to evaluate correlates of occupational outcomes after KTX. Methods: We included 336 working-age patients with at least one creatinine assessment in the 3-month screening period. We collected clinical information from medical records. All subjects answered a self-administered questionnaire, and a follow-up questionnaire was mailed to each participant after 6 months. Study outcomes were the Work Ability Index (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 29 publications
8
31
1
1
Order By: Relevance
“…Additionally, a high SPH 6 month post-Tx predicted being employed 12 months post-Tx. This is in line with Sangalli et al [11] who showed in a follow-up study post-Tx that good physical health perception enhances the chances of being employed.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Additionally, a high SPH 6 month post-Tx predicted being employed 12 months post-Tx. This is in line with Sangalli et al [11] who showed in a follow-up study post-Tx that good physical health perception enhances the chances of being employed.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with most return to work studies taking pre-Tx employment status into account [47, 911], pre-Tx employment was the strongest predictor for post-Tx employment. 81% of the patients who were employed pre-Tx were employed 12 month post-Tx, versus 18% of those who were not employed pre-Tx.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations